Poland: from a Transit Country to a Logistics Hub in Central Europe - S. A. Kuvaldin (Международная аналитика, 2025)
Starting from the first decade of the 21st century, the political elites of Poland have made various efforts to change its position as a transit territory between Germany and Russia, as well as to reduce dependence on both countries. The ‘Law and Justice’ party, traditionally opposed to the development of cooperation with both Russia and Germany, was particularly active in this direction. The article analyzes Poland’s major infrastructure projects in recent years that affect its logistics capabilities.Specifically, the creation of new routes for transporting hydrocarbons, the emergence of new rail and road networks, the development of port infrastructure, and the construction of new waterways are discussed. The analysis concludes that most of these projects align with the EU’s overall goals of improving connectivity among member states. The significant cost of many of these projects suggests that they would have been practically impossible to implement without financial support from EU structural funds. This is particularly evident in the example of the ‘Via Carpatia’ highway project, which was conceived in the first decade of the 21st century but was not actually developed until the EU showed interest in it. In this context, intergovernmental foreign policy organizations involving Poland, such as the Three Seas Initiative, can be considered primarily as a lobbying tool within the EU for intergovernmental infrastructure projects in Central and Southern Europe.At the same time, Poland is developing the infrastructure of its Baltic ports, which have the potential to compete with Germany’s container terminals in the North Sea. The launch of some of Poland’s high-profile initiatives in the field of shipping can be seen as primarily driven by domestic political goals aimed at demonstrating a commitment to increasing Poland’s sovereignty, rather than being economically justified. Overall, Poland’s efforts are focused on leveraging its strategic access to the Baltic Sea to create logistical corridors to continental Central European countries.